2015
DOI: 10.1016/j.ecss.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton blooms in estuarine and coastal waters: Seasonal patterns and key species

Abstract: Phytoplankton blooms are dynamic phenomena of great importance to the functioning of estuarine and coastal ecosystems. We analysed a unique (large) collection of phytoplankton monitoring data covering 86 coastal sites distributed over eight regions in North America and Europe, with the aim of investigating common patterns in the seasonal timing and species composition of the blooms. The spring bloom was the most common seasonal pattern across all regions, typically occurring early (February-March) at lower lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 228 publications
(137 citation statements)
references
References 63 publications
6
125
2
4
Order By: Relevance
“…6). Carstensen et al (2015) reported that PPL blooms were mainly composed of diatoms and dinoflagellates throughout the salinity gradient (0-33) in eight estuaries located north of 30°N in North America and Europe, as also found during the present study. They also reported the spatial distributions of Skeletonema costatum (Grev.)…”
Section: −1supporting
confidence: 71%
See 3 more Smart Citations
“…6). Carstensen et al (2015) reported that PPL blooms were mainly composed of diatoms and dinoflagellates throughout the salinity gradient (0-33) in eight estuaries located north of 30°N in North America and Europe, as also found during the present study. They also reported the spatial distributions of Skeletonema costatum (Grev.)…”
Section: −1supporting
confidence: 71%
“…dominated at the same salinity levels as those described above. Because of their species-specific salinity tolerances (Kirst 1989), PPL taxa appeared at different salinity levels in Lake Furen, as has been observed in many other estuaries (Brand 1984, Rijstenbil 1988, Marshall & Alden 1990, Mallin 1994, Litaker et al 2002, Shikata et al 2008, Carstensen et al 2015.…”
Section: −1mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we developed four new indicators for microbes (bacteria and cyanobacteria), but their poor score on pressure responsiveness and the potential to set targets indicated a need for further development and validation . Some phytoplankton biomass indicators, such as chlorophyll-a concentration from satellite measurements, provide valuable assessments of pressures leading to eutrophication, but linking changes in diverse and rapidly fluctuating phytoplankton composition with impacts of nutrient loading has proved challenging Carstensen et al, 2015).…”
Section: Development Of New Indicatorsmentioning
confidence: 99%